The Determinant of Loan Portfolio Shifting: Empirical Study of Banks in ASEAN Country - Foza Hadyu Hasanatina (JURNAL BISNIS STRATEGI, 2023)
Standard Basel regulations limits banks to manage loan activity. It is about minimal capital requirements and liquidity aspect. Bank have to manage the loan portfolio to avoid risk in aspects. This study examines the determinants of loan portfolio shifting of banks, such as: interest rate and credit risk. This study also adds profitability ratio as moderating variable to examines the role on the effect of determinants. The population of this study is commercial banks in ASEAN countries. The sample selection uses non-probability sampling technique with several predetermined characteristics (Cooper & Schindler, 2003). Characteristics of the sample selection are banks categorized as commercial banks by Osiris Database; commercial banks, the region is ASEAN countries; and fortunately for availability data in commercial loans and real estate loans for at least three consecutive years during 2016-2020. The total samples obtained are 72 commercial banks in ASEAN countries. This study uses Ordinary Least Square (OLS) with unbalance pooled panel data. The results show that interest rate has an impact in loan portfolio shifting. However, credit risk has not significantly impact on loan portfolio shifting. In the term of the role in profitability, the effect of interest rate and credit risk is higher on more profitable banks.